Research on Algorithms for Multi-Vector Attitude Determination. (14th September 2022) - Liu, Yilin; Yu, Ruihang; Xiong, Zhiming; Guo, Yan
Abstract : Various attitude estimation methods are based on an optimization problem posed in 1965 by Grace Wahba, which is called Wahba's problem in the field of attitude estimation. As a key for attitude determination, many different algorithms for minimizing Wahba's loss function have been proposed in the past 60 years. Among the most representative are Quaternion Estimator (QUEST), Singular Value Decomposition (SVD), and Fast Optimal Attitude Matrix (FOAM), which are briefly introduced in this research paper, and new algorithms proposed in recent years such as Fast Linear Quaternion Attitude Estimator (FLAE), are also included. The calculation principle and derivation process are given in the article, and simulation under high noise conditions for algorithms mentioned has been completed. Finally, several practical engineering applications related to Wahba's problem are introduced and the future development trend of attitude estimation is discussed.